Computer numerical control [ - Cook, Jerome T.; Lynch, Mike (Fundamental manufacturing processes, 2002)
Provides an introduction to the basic principles of computer numerical control (CNC), a process widely used in the manufacturing industry. Features segments on the rectangular coordinate system, program zero, axes of motion, point-to-point positioning, contouring, interpolation, and program command lines, as well as manual programming and computer-aided design and manufacturing